Melatonergic drugs in clinical practice - Hardeland, Rüdiger; Poeggeler, Burkhard; Srinivasan, Venkataramanujan; Trakht, Ilya; Pandi-Perumal, Seithikurippu R; Cardinali, Daniel P (Arzneimittel-Forschung, 2008)
Melatonin (CAS 73-31-4) has both hypnotic and sleep/wake rhythm regulating properties. These sleep promoting actions, which are already demonstrable in healthy humans, have been found useful in subjects suffering from circadian rhythm sleep disorders (CRSD) like delayed sleep phase syndrome (DSPS), jet lag and shift-work sleep disorder. Low nocturnal melatonin production and secretion have been documented in elderly insomniacs, and exogenous melatonin has been shown to be beneficial in treating sleep disturbances of these patients. In comparison to a number of sleep-promoting compounds that are usually prescribed, such as benzodiazepines and z-drugs (zolpidem and zopiclon belonging to the latter ones), melatonin has several advantages of clinical value: it does not cause hangover nor withdrawal effects and is devoid of any addictive potential. However, recent meta-analyses revealed that melatonin is not sufficiently effective in treating most primary sleep disorders. Some of the reasons for a limited efficacy of this natural hormone are related to its extremely short half-life in the circulation, and to the fact that sleep maintenance is also regulated by mechanisms downstream of primary melatonergic actions. Hence, there is an urgent need for the development of melatonin receptor agonists with a longer half-life, which could be suitable for a successful treatment of insomnia. Such requirements are fulfilled by ramelteon (CAS 196597-26-9), which possesses a high affinity for the melatonin receptors MT1 and MT2 present in the circadian pacemaker, the suprachiasmatic nucleus (SCN). Ramelteon also has a substantially longer half-life than melatonin. This new drug has been successfully used in treating elderly insomniacs without any adverse effects reported, and is promising for treating patients with primary insomnia and also those suffering from CRSD. Since sleep disturbances constitute the most prevalent symptoms of various forms of depression, the need for the development of an ideal antidepressant was felt, which would both improve sleep and mitigate depressive symptoms. Since most of the currently used antidepressants, including the selective serotonin re-uptake inhibitors worsen the sleep disturbances of depressive patients, another novel melatonergic drug, agomelatine (CAS 138112-76-2), holds some promise because of its particular combination of actions: it has a high affinity for MT1 and MT2 receptors in the SCN, but it acts additionally as a 5-HT(2C) antagonist [5-hydroxytryptamine (serotonin) receptor 2C antagonist]. The latter property, which is decisive for the antidepressive action, would not favor but potentially antagonize sleep, but this is overcome during night by the melatonergic, sleep-promoting effect. This drug has been found beneficial in treating patients with major depressive and seasonal affective disorders. Unlike the other antidepressants, agomelatine improves both sleep and clinical symptoms of depressive illness and does not have any of the side effects on sleep seen with other compounds in use. This property seems to be of particular value because of the aggravating effects of disturbed sleep in the development of depressive symptoms. Based on these facts, agomelatine seems to be a drug of superior efficacy with a promising future in the treatment of depressive disorders. However, long-term safety studies are required for both ramelteon and agomelatine, with a consideration of the pharmacology of their metabolites, their effects on redox metabolism, and of eventual undesired melatonergic effects, e. g., on reproductive functions. According to current data, both compounds seem to be safe during short-term treatment